Interleaved Boost Converter Fed with PV for Induction Motor/Agricultural Applications - Adireddy Ramesh; M. Siva Kumar; O. Chandra Sekhar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
In present Electricity market Renewable Energy Sources (RES) are gaining much importance. The most common Renewable Energy Sources are Photo voltaic (PV), fuel cell (FC) and wind energy systems, out of these three PV systems PV system can implemented in most of the locations. Due to the power cuts and power disturbances in Distribution systems agriculture application is concentrated on PV based Energy system. The use of PV system is increasing day by day in agriculture application, due to their ease of control and flexibility. PV Electrification schemes also involves various subsidies in government national and international donors. Especially in Agriculture field by use of PV one can achieve higher subsidy. The output of PV system is low voltage DC to have high efficiency. The motors used in agriculture field are Induction Motors (IM) fed from Three phase AC supply, to boost the PV output we need a high voltage gain boost converter along with PWM inverter to Induction motor drive. Out of various DC-DC converter configurations interleaved boost converter is gaining much attention, due to its reduction in size and Electromagnetic Interference (EMI). In this work we are proposing a PV fed interleaved boost converter with PWM inverter for agriculture applications. The design process of interleaved boost converter is explain detail and compared with existing boost converter. A 10KW Power rating is choosing for the Induction motor drive and design calculations are carried out. A MATLAB/SIMULINK based model is developed for boost and interleaved boost converter and simulation results are presented, finally a scaled down hardware circuit design for interleaved boost converter and results are presented.